Prevalence of dural venous sinus stenosis and hypoplasia in a generalized population. (8th January 2016) - Durst, Christopher R; Ornan, David A; Reardon, Michael A; Mehndiratta, Prachi; Mukherjee, Sugoto; Starke, Robert M; Wintermark, Max; Evans, Avery; Jensen, Mary E; Crowley, R Webster; Gaughen, John; Liu, Kenneth C
Abstract : Background and purpose: While recent literature has described the prevalence of transverse sinus stenosis in patients with idiopathic intracranial hypertension, tinnitus, and refractory headaches, it is unclear what the prevalence is in the general population. This study evaluates the prevalence of venous sinus stenosis and hypoplasia in the general patient population. Materials and methods: 355 of 600 consecutive patients who underwent CT angiography of the head met the inclusion criteria. The diameters of the dural venous sinuses were recorded. Each study was evaluated by a neuroradiologist for the presence of stenoses. Univariate and multivariate statistical analyses were performed by a statistician. Results: The prevalence of unilateral transverse sinus stenosis or hypoplasia in a sample of patients representing the general population was 33%, the prevalence of bilateral transverse sinus stenosis was 5%, and the prevalence of unilateral stenosis with contralateral hypoplasia was 1%. A multivariate analysis identified arachnoid granulations as a predictor of stenosis (p<0.001). Gender trended toward significance (p=0.094). Race was not a significant predictor of stenosis (p=0.745). Conclusions: The prevalence of bilateral transverse sinus stenosis in the general population is not trivial. These data may be used as a reference for understanding the mechanistic role of stenoses in idiopathic intracranial hypertension, tinnitus, and refractory headaches.